The integration of Fuzzy FMEA and AHP methods for optimizing of logistic systems - Panudju, Andreas Tri; Mahuda, Isnaini; Marfuah, Umi; Mutmainah, Mutmainah; Sudarwati, Wiwik (Journal Industrial Servicess, 2024)
This study seeks to enhance the logistics system of a logistics company through the integration of Fuzzy FMEA and AHP methodologies. The focus is on optimizing efficiency and quality within the logistics system to meet competitive market demands. The issue at hand is the potential for breakdowns in manufacturing and distribution processes, which may impede overall performance. The aim is to detect possible failures, assess failure risks using the Fuzzy FMEA method, and improve decision-making through the AHP method. The research methodology includes a literature review, data analysis, and the use of Expert Choice software for weight calculations and rankings. Data were collected from the decision-makers involved in the company. The findings show that the integration of Fuzzy FMEA and AHP methodologies can effectively identify potential failures, assess risks with greater accuracy, and prioritize improvement measures within the logistics framework of a traditional bag factory. In summary, the integration of Fuzzy FMEA and AHP methodologies can enhance risk management and decision-making within the logistics system, mitigate failure risks, optimize production and distribution processes, and more effectively meet client requirements. This integration presents an innovative approach to improving logistics systems.